The effect of excretory/secretory product released by L3 of A. galli on villous compact in intestine of laying hens - Ummu Balqis; . Darmawi; Risa Tiuria; Bambang P. Priosoeryanto (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The nematode, Ascaridia galli, caused pathological changes in the gut, while the larval development takes place in the intestine epithelium. The aim of this research was to examine the effect of excretory/secretory product released by L3 of A. galli to prevent intestine destructions based on villous compact in duodenum, jejunum, and ileum of laying hens. Excretory/secretory was prepared from metabolic of L3 released in culture médium in flasks containingrosswell park memorial institute (RPMI) 1640 media, pH 6.8, without phenol red. Excretory/secretory product was concentrated with vivaspin 30.000 MWCO. The chickens vaccinated with 80 g protein excretory/secretory in crudemixed with Fruend Adjuvant Complete and repeated three times with dose of each 60 g mixed with Freund Adjuvant Incomplete with an interval of one week intra muscularly. The chickens were challenged with 1000 infective larvae A. galli one week later. After two weeks the chickens were operated. Villous compact in duodenum, jejunum, and ileum of laying hens were analyzed. The result showed that immunization was able to sustained significantly intestinevillus compact, particularly in duodenum. This research concluded that the excretory/secretory product could protect villus in duodenum against parasitic diseases caused by A. galli.